Cloud Kitchen: Strategy for Indonesian Culinary Business (SMEs) Growth During and Post Pandemic Era - Helen Dian Fridayani; Muhammad Iqbal; Muhammad Eko Atmojo (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
This study aims to examine cloud kitchens that are widely applied in the world which can be a strategy for developing the culinary business in Indonesia, especially during and post the COVID-19 pandemic. Cloud kitchens are often referred to as satellite kitchens or ghost kitchens. Cloud kitchen is a restaurant with a concept that only offers delivery services and does not provide on-site dining facilities. The method used in this research is literature review of several documents, regulations, and journals, both print and online media which are reduced to a research data that can be presented scientifically. The result is that the cloud kitchen is one of the promising businesses during a pandemic and can be developed after a pandemic. Several delivery services such as Gojek and GoFood in collaboration with the Rebel Food company have succeeded in opening several cloud kitchen locations in Indonesia, especially big cities such as Jakarta, Bandung and Surabaya. As a result, the could kitchen can help SMEs in running a business in the culinary field more effectively and efficiently. However, the problems that arise in some areas, especially marginalized and remote areas are still not reachable, this is certainly a challenge with GoFood and also the government to expand the location to reach many SMEs in Indonesia. This research is expected to contribute to the development of economics as a strategy for community economic recovery.